Prototype Aplikasi Edukasi Cyberbullying Berbasis Mobile Android - Fiki Nur Rahman; Shendy Aditayahya Wardana; Pradityo Utomo (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
As technology develops rapidly, it has not only positive but also negative impacts; one of the negative impacts is the case of cyberbullying. Cyberbullying is an unpleasant action towards other people on the internet. One way to reduce cyberbullying is to create educational applications about cyberbullying. This application will provide an explanation of what cyberbullying is and how to prevent cyberbullying by providing an explanation that is light and easy to understand. This application is based on Android mobile, so it can more easily reach more users, using Java programming and display design using figma.